Data warehouse model for monitoring key performance indicators (KPIs) using goal oriented approach - Abdullah, Mohammed Thajeel; Ta'a, Azman; Abu Bakar, Muhamad Shahbani (AIP Publishing LLC, 2016)
The growth and development of universities, just as other organizations, depend on their abilities to strategically plan and implement development blueprints which are in line with their vision and mission statements.The actualizations of these statements, which are often designed into goals and sub-goals and linked to their respective actors are better measured by defining key performance indicators (KPIs) of the university. The proposes ReGADaK,which is an extended the GRAnD approach highlights the facts, dimensions, attributes, measures and KPIs of the organization. The measures from the goal analysis of this unit serve as the basis of developing the related university’s KPIs.The proposed data warehouse schema is evaluated through expert review, prototyping and usability evaluation.The findings from the evaluation processes suggest that the proposed data warehouse schema is suitable for monitoring the University’s KPIs.